CHARACTERISTICS OF NATURAL LIGHT OPENINGS ON ROSTER WALLS IN RESIDENTIAL HOMES IN BANDUNG - Arditra
Natural illumination is an essential component in architecture, particularly in residential structures where occupants spend substantial time engaging in various activities. This research concentrates on the application of latticework as a facade element in residential buildings, which has not been fully optimized, especially concerning natural lighting. The apertures within the latticework can substantially enhance a building's performance. Critical factors such as the inclination angle of the slats, orientation relative to cardinal directions, and the dimensions of the latticework must be carefully considered, as they significantly impact the effectiveness of natural light ingress into residential structures in Bandung, located at 6° S of the equator. The research questions addressing the quantity and quality of natural lighting are crucial, as both aspects are vital for fostering a comfortable and energy-efficient environment. The quantity of natural lighting pertains to the volume of light penetrating a space, whereas its quality is associated with the distribution of light. The research methodology includes digital modeling and computational simulation using Rhinoceros version 7, incorporating local climate data from Bandung's EPW datasets covering the years 2007 to 2021. This investigation also involves full-scale laboratory measurements with a latticework prototype illuminated by three 225-watt LED lamps to assess natural lighting performance directly, with measurements obtained using a lux meter. Laboratory assessments and simulations are conducted within a room measuring 3 meters in length, width, and height, oriented eastward. Research parameters focus on room illuminance levels and annual sunlight percentages expressed in UDI, DA, and DF metrics. The study is executed based on six extreme annual conditions occurring on May 25, March 4, June 21, March 21, September 21, and December 21. The analysis juxtaposes shading and reflection concepts, alongside comparisons using conventional latticework and standard windows of dimensions 1.2 m x 0.6 m and 3 m x 3 m. Findings reveal that latticework employing the reflection concept achieves superior natural lighting intensity compared to the shading concept, whereas the shading approach demonstrates enhanced quality in light distribution.